2016
DOI: 10.1155/2016/3539748
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Buzui on Acute Alcoholism in Mice

Abstract: This study was designed to investigate the role of a traditional buzui recipe in anti-inebriation treatment. Buzui consists of Fructus Schisandrae Chinensis, Fructus Chebulae, Fructus Mume, Fructus Crataegi, Endothelium Corneum Gigeriae Galli, and Excrementum Bombycis. The buzui mixture was delivered by gavage, and ethanol was delivered subsequent to the final treatment. The effects of buzui on the righting reflex, inebriation rates, and the survival curve are depicted. Blood alcohol concentrations, alanine am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…As showed in Table 3 , there was a significant rise of levels of AST and ALT in serum 6 h after alcohol consumption (control group) when compared with the normal group. In the literature [ 18 , 19 , 20 ], 6 h were usually adopted for evaluation of AST and ALT levels, and some researchers even found that the level of ALT was the highest among 1.5, 3, 6, 12 h [ 21 ]. For treatment groups, ban sha herbal infusion, sprite, and fresh orange juice obviously increased the level of AST, while green tea, honey chrysanthemum tea, jasmine tea, and soda water markedly decreased the level of AST in serum.…”
Section: Resultsmentioning
confidence: 99%
“…As showed in Table 3 , there was a significant rise of levels of AST and ALT in serum 6 h after alcohol consumption (control group) when compared with the normal group. In the literature [ 18 , 19 , 20 ], 6 h were usually adopted for evaluation of AST and ALT levels, and some researchers even found that the level of ALT was the highest among 1.5, 3, 6, 12 h [ 21 ]. For treatment groups, ban sha herbal infusion, sprite, and fresh orange juice obviously increased the level of AST, while green tea, honey chrysanthemum tea, jasmine tea, and soda water markedly decreased the level of AST in serum.…”
Section: Resultsmentioning
confidence: 99%
“…We measured blood ALT and AST concentration at 1, 3, and 5 h after EtOH administration. Usually, 6 h has been used for evaluation of ALT and AST levels [ 34 , 38 ]. In mice injected intraperitoneally with a single EtOH dose, ALT and AST were increased at 8 h and 12 h after administration, respectively [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the alcoholic liver injury mouse model, the P. mume formula also exhibited hepatoprotective effects (Chen et al, 2016). Khan et al (2017) investigated the molecular mechanism using a metabolic approach.…”
Section: Liver Protectionmentioning
confidence: 99%